Against Rehabilitated Killjoys: Cripping Feminist Geographies of Academic Care - Clancy, Erin (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Autoethnographic scholarship helps account for the conditions of harm, care, and resistance in academic spaces within the ‘neoliberal university’, yet interventions can be limited by normative care frameworks that reinscribe ableist logics. This paper focuses on this genre of scholarship in feminist geography, here referred to as feminist geographies of academic care, and the ways attempts at resolving the academic “care crisis” get diverted and (re)oriented toward institutional ends. I use “disability as methodology” to read if, and how the system of (dis)ability structures and enmeshes the university’s imperative of rationality with ambivalent feminist desires for belonging and something else. In turn, a clear rehabilitative narrative arc emerges in this literature that indexes better futures through social cohesion and the (implicit) absence of mental disability and neurodivergence. I argue that this narrative prioritizes attachment to the university over those most harmed by it, but which can be disrupted through trans/crip and neuroqueer dispositions.